Identification of tRNA-Related Fragments and Their Potential Regulatory Effects in Thyroid-Associated Ophthalmopathy - Yue, Zifan; Tong, Fei; Zeng, Chengcheng; Wei, Ruili (Frontiers in Genetics, 2022)
Recently, the potential role of tRNA-related fragments (tRFs) in ophthalmic diseases has been extensively researched. However, systematic studies on the potential regulatory effects of tRFs in thyroid-associated ophthalmopathy (TAO) are lacking. We used high-throughput sequencing techniques to measure expression levels of mRNAs and tRFs in patients with TAO, and the results were verified by real-time quantitative reverse transcription polymerase chain reaction (q-PCR). Next, the potential biological regulatory effect of differentially expressed tRFs was analyzed, and potential downstream target RNAs of differentially expressed tRFs were predicted to explore the potential role of tRFs as therapeutic targets and biomarkers of TAO. A total of 50 tRFs and 361 mRNAs were dysregulated in the TAO group, and tRF5-GluCTC, PMAIP1, HSD17B2 and ATF3 were verified to be significantly differentially expressed in TAO. Our research reveals that several associated pathways likely play a role in the pathogenesis of TAO. By targeting ATF3 and HSD17B2, tRF5-GluCTC may play a significant role in regulating the orbital fibroblast adipogenic response in patients with TAO.